AB052. The Human Variome Project (HVP) and the HVP ASEAN Node - Alwi, Zilfalil Bin (Ann Transl Med, 2015)
The Human Variome Project (HVP) is an international NGO that is working to build capacity in responsible clinical genomics around the world. Founded in 2006, and lead in its early years by Professor Richard Cotton, the Project has grown to become a global movement with over 1,300 individual members from 81 countries and close to 200 data provider members. The project works to ensure that the lack of access to information on genetic variants and their effects on human health is not an impediment to diagnosis and treatment. Together with partner organisations including national and regional human genetics societies, national governments and intergovernmental organisations such as UNESCO—of which the HVP is an NGO official partner—the project establishes standards, guidelines and best practices for the responsible development and operation of genetic variation data sharing infrastructure, facilitates training and education of the public and the clinical genomics field and assists in embedding data sharing into routine clinical practice. The HVP believes that the free and open sharing of genetic variation is fundamental to providing quality clinical care. To ensure that this data can be collected, curated, interpreted and shared in a responsible manner that is respectful of the diverse ethical, legal and social differences of its member countries, the HVP works with local stakeholders in each country to establish HVP Country Nodes. An HVP Country Node is defined as having three components: (I) a repository, or linked network of databases, that collect and store information on variation in the human genome that has been generated within each country and that enables the sharing of that information both nationally and internationally; (II) a governance structure that ensures that the work of the Node is both sustainable in the long term and is consistent with all relevant national and international ethical, legal and social requirements; and (III) a set of policies and procedures that ensures that the repository is operated and maintained in a responsible and accountable manner that is consistent with both national and HVP Standards. The HVP Malaysian Node (MyHVP), one of 23 HVP Country Nodes currently in existence, was established in 2010 and officially launched by Professor Cotton. The MyHVP database was made available on the internet a year later. The HVP Malaysian Node has taken a key role in the region and has worked to establish the HVP ASEAN Regional Node. Among its objectives is to foster closer collaboration among ASEAN member states on issues relating to data sharing, data basing and variant interpretation expertise, resources and technical facilities. The HVP ASEAN Regional Node also provides help with capacity building and training, especially to less well-resourced countries in the South East Asian region, for example Cambodia, Laos, and Myanmar. The HVP ASEAN Regional Node was launched in 2013 at Universiti Sains Malaysia, Kota Bharu, Malaysia. Representatives from Thailand, Vietnam, Singapore, Brunei, Indonesia, Philippines and the international Human Variome Project were represented. This presentation will provide an in-depth overview of the HVP ASEAN Regional Node and its progress to date.